The Effectiveness of the Integrated Intervention of Joint Sexual Therapy and Satir Model on Sexual Satisfaction and Marital Silence of Couples With Sexual Dissatisfaction - Torkashvand , Fatemeh; Davoodi, Hossein; Taghvaei , Davood (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of this research was to determine the effectiveness of the integrated intervention of joint sexual therapy and Satir model on sexual satisfaction and marital silence of couples with sexual dissatisfaction.Method: The research method was quasi-experimental with experimental and control groups. The statistical population of this research included all couples who referred to counseling centers in Malayer city in 2022. 30 couples were selected as available and were replaced in two experimental (15 couples) and control (15 couples) groups randomly and by lottery method. The combined intervention of joint sex and Satir therapy was performed in 9 sessions twice a week for 90 minutes. Then both experimental groups participated in the post-test phase and after 3 months the follow-up phase was done. Rezaei and Rasouli's sexual satisfaction questionnaire (2018) and Larson's sexual satisfaction questionnaire (1998) were used to collect data. In order to analyze the data, descriptive statistics tests (mean and standard deviation) and analysis of variance with repeated measurements and SPSS version 24 software were used.Results: The results showed that the combined intervention of joint sexual and sexual therapy had an effect on reducing marital silence (F= 49.26) and increasing sexual satisfaction (F=179.54) of couples (P